Short-term and Long-term Clinical Outcomes of Combined Caudate Lobectomy for Intrahepatic Cholangiocarcinoma Involving the Hepatic Hilus: A Propensity Score Analysis - Di Zeng; Yaoqun Wang; Ningyuan Wen; Bei Li; Nansheng Cheng; Jiong Lu (Gut and Liver)
Background/Aims: Extended hepatectomy combined with caudate lobe resection has been approved for the radical resection of hilar cholangiocarcinoma. There was a lack of credible research on the clinical value of caudate lobectomy (CL) for intrahepatic cholangiocarcinoma involving the hepatic hilus when combined with hepatectomy. We aimed to compare the short-term and long-term outcomes of the combined procedure with those of only CL for curative resection of intrahepatic cholangiocarcinoma involving the hepatic hilus. Methods: This single-center retrospective cohort study of patients with hilar cholangiocarcinoma was conducted from January 2007 to December 2021. Patients who underwent radical resection were enrolled in this study. The short-term and long-term clinical outcomes of the groups were compared before and after propensity score matching (PSM). Results: A total of 282 patients were included. There were no statistically significant differences in perioperative clinical outcomes between the CL group and the non-CL group before and after PSM. Compared to patients in the non-CL group, patients in the CL group had significantly longer overall survival before and after PSM (p=0.007 before PSM, p=0.033 after PSM). Moreover, compared to the non-CL group, the CL group had longer disease-free survival before and after PSM (p<0.001 before PSM, p=0.019 after PSM). Conclusions: The postoperative complications of the CL group were comparable to those of the non-CL group. CL improved the long-term survival of patients with intrahepatic cholangiocarcinoma involving the hepatic hilus when combined with hepatectomy. Therefore, hepatectomy combined with caudate lobe resection should be performed for patients with hilar cholangiocarcinoma.